Use of artificial intelligence in documentary information systems. A systematic literature review 2013-2023 (Ágora de Heterodoxias, 2024)
In the last decade, Artificial Intelligence (AI) has experienced notable growth in its application in Documentary Information Systems (DIS), offering more effective and advanced solutions to manage and analyze large volumes of information. In this article, the product of previous research, a Systematic Literature Review (SLR) was carried out focused on the use of AI in DIS between 2013 and 2023, compiling research from EBSCO, Scopus, and Web of Science. The PRISMA 2020 methodology was applied using NVivo for qualitative analysis and Excel together with Microsoft Power BI for quantitative analysis. 22 articles and 117 references were identified, highlighting impacts such as efficient management, search and retrieval of information, transparency, and data quality. Key trends include document lifecycle automation, information management model changes, AI ethics policies in DIS, data organization, and machine learning applications. This rigorous review synthesizes the available evidence, providing clear and useful findings for the academic community and institutions committed to operational efficiency and information transparency, contributing to Sustainable Development Goal 16.6 and facilitating decision-making.
Keywords: artificial intelligence; document management systems; systematic literature review